The Alteration of Circulating Lymphocyte Subsets During Tacrolimus Therapy in Neuromyelitis Optica Spectrum Disorder and Its Correlation With Clinical Outcomes - Wang, Liang; Huang, Wenjuan; ZhangBao, Jingzi; Chang, Xuechun; Tan, Hongmei; Zhou, Lei; Lu, Chuanzhen; Wang, Min; Lu, Jiahong; Zhao, Chongbo; Quan, Chao (Frontiers in Neurology, 2022)
Objectives: We aimed to explore the alteration of circulating lymphocyte subsets before and after tacrolimus (TAC) therapy in neuromyelitis optica spectrum disorder (NMOSD) and its correlation with clinical outcomes. Methods: Anti-aquaporin-4 antibody (AQP4-ab)-positive NMOSD patients treated with TAC were followed and clinically evaluated at 0, 3, 6, 12 months after initiation of TAC. Flow cytometry was employed to detect the proportion of various whole blood lymphocyte subsets at every time point. Correlation analysis was further performed to explore the association between annualized relapse rate (ARR), the Expanded Disability Status Scale (EDSS) score and the proportion of circulating lymphocyte subsets before and after TAC therapy. Results: Thirteen eligible NMOSD patients were included. The proportion of CD19+CD24hiCD38hi/CD19+ and CD19+CD5+CD1dhi/CD19+ lymphocyte subsets increased significantly after TAC therapy (p=0.010 and p<0.001). The proportion of CD19+BAFFR+, CD19+IFN-γ+ and CD19+IL-10+ subsets decreased significantly after TAC therapy (p=0.015, 0.018 and 0.042 respectively). There was a negative correlation between CD4+CD25hi subset and EDSS score (p=0.016, r=-0.652). Conclusion: Possibly through increasing regulatory B and suppressing BAFFR+ B and IFN-γ+ B subsets, TAC could decrease relapse. EDSS score may be correlated with some lymphocyte subsets after TAC therapy.